1981
DOI: 10.1088/0022-3727/14/8/016
|View full text |Cite
|
Sign up to set email alerts
|

Response of Schottky barrier solar cells at higher temperatures

Abstract: The responses of Cu/Cr-p-type silicon and Au-n-type silicon Schottky barrier solar cells at higher temperatures have been studied. The variations of different factors, such as intrinsic carrier density, energy gap, absorption coefficient, barrier height, effective number of photons etc., have been taken into account. The results show that in the temperature range 300-450K, except for the short-circuit current, all other factors (e.g. open-circuit voltage, fill-factor and conversion efficiency) decrease with in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 15 publications
3
20
0
Order By: Relevance
“…Thus, bifacial devices that are relatively thin function better than those that are substantially thicker. These results support earlier findings [ 11,20 ] that have been published. There are serious defects in every material.…”
Section: Resultssupporting
confidence: 94%
“…Thus, bifacial devices that are relatively thin function better than those that are substantially thicker. These results support earlier findings [ 11,20 ] that have been published. There are serious defects in every material.…”
Section: Resultssupporting
confidence: 94%
“…Several parameters, namely, a , b , H , and α, are needed to calculate the EM enhancement factor ( R ). The molecular polarizability of 9.73 Å 3 for 1-propanethiol was taken from ref . An order of magnitude change in α did not seriously affect the calculated enhancement (∼1%), however.…”
Section: Resultsmentioning
confidence: 99%
“…These parent compounds are known to be an excellent double exchange system with a non-magnetic A-site (La 3+ ). In many cases, it has been found that doping with rare earth ions influences and enhances the colossal magnetoresistive properties of the systems [3,8,13] besides having a strong effect on the other magnetic and electronic properties. However, most of the studies were performed on bulk manganite systems.…”
Section: Introductionmentioning
confidence: 99%